Bioinspired 1D Superparamagnetic Magnetite Arrays with Magnetic Field Perception. Issue 32 (27th May 2016) - Jiang, Xiangyu; Feng, Jiangang; Huang, Lei; Wu, Yuchen; Su, Bin; Yang, Wensheng; Mai, Liqiang; Jiang, Lei
Abstract : Superparamagnetic magnetite nanoparticles can be assembled into 1D arrays by a capillary‐bridge mediate assembly approach, inspired by the Earth's magnetic field perception in nature. These 1D arrays possess strict alignment, precise position and high aspect ratio, yielding highly anisotropic magnetization characteristic.